Manifestações musculoesqueléticas persistentes pós-febre chikungunya: uma série de casos em um estado do Nordeste brasileiro - Debbo, Alejandra (2019)
Chikungunya fever (CF) is an arbovirus caused by the chikungunya virus (CHIKV). Having as a main characteristic, joint pain and possible chronicity in more than half of infected patients. The purpose of the present study is to evaluate the persistent musculoskeletal manifestations of CF. These are a series of cases. It was evaluated a sample of 72 patients with persistent musculoskeletal disease (≥ 1 month) after the confirmation of CF by laboratory tests. These patients were monitored for 12 months and were treated at the ambulatory clinic of the University Hospital of the Federal University of Sergipe (HU / UFS). Patients were evaluated at admission, at 1 month, 2 months, and then every 3 months until 12 months. In all consultations, it was examined painful and / or swollen joints, periarticular symptoms, other important physical examination findings and VAS (visual analogue pain scale). Main results: 84.7% were female patients; the average age was 53.8 years; the average time of musculoskeletal complaints was 6 months. Comorbidities were present in 61.1% of patients and previous musculoskeletal disease was present in 69.4%. The most frequent presentation at admission was polyarticular in 76.4%. The most affected joints were: hands, knees, ankles and feet. VAS on admission was intense in most patients: 66.7%. Tenosynovitis was present in 44.5% of the patients, with ankles being more frequent. Corticosteroids were used in 65.3% of patients and chloroquine in 31.98%. It was concluded that persistent musculoskeletal manifestations after CF are frequent. After 12 months of monitoring, more than half of the patients maintained some complaint, and 33.3% of patients maintained pain mainly in the form of diffuse pain even with regular treatment and monitoring.